Sistem Rekrutmen Calon Legislatif DPRD Provinsi Jawa Tengah Periode 2014- 2019. Studi kasus: DPD PDI-Perjuangan Jawa Tengah - Adi Yoga; Dzunuwanus Ghulam Manar; Susilo Utomo (Journal of Politic and Government Studies, 2014)
ABSTRACTIn order to perform perspective legislative members, political party mustapply strict system on recruitment. It is also important in order to perform publicofficials who have capability.According to Arend Lijphart political party consolidation happens withinsocial gangs in the society. Political party also recruits cadres in order to beparticipated in the election. Also recruitment held by political party is veryimportant to select best cadres for executive offices. This function can bemeasured to identify political party performances within democratic country.The research use descriptive qualitative method where data get frominterview and document.Based on the findings of the field, in accordance with the Decree No. 061 /TAP / DPP / III / 2013, the PDI-Struggle in recruiting cadres prioritize legislativecandidates from the party of structural board began PAC levels to DPD as a toppriority the recruitment and incumbent or legislative candidates who already holdlegislative seats in Central Java Provincial Parliament.Result show that Indonesia Democratic Party Struggle in local area refersto SK No. 061 / TAP / DPP / III / 2013 on reality legislative member candidateshowever, the letter is tactical and it is possible for improvisation in thisrecruitment.Key Words: Indonesian Democratic Party of Struggle in Central Java, Legislatives Candidate, Recruitment System